Tradução, adaptação cultural e validação de um instrumento para avaliação do sono em terapia intensiva no Brasil: questionário de sono de Richards-Campbell - Brito, Rogleson Albuquerque (2019)
Evidence indicates that poor quality of sleep is frequent in the hospital environment, particularly in intensive care units (ICUs). In view of the need for more adequate tools to evaluate critical patients' sleep. The aim of the present study was to translate into Portuguese, to culturally adapt and validate for use in Brazil, a questionnaire originally developed in English, the Richards-Campbell Sleep Questionnaire (RCSQ). The study consisted of the following steps: translation, back translation, cultural adaptation, reproducibility and validation. The concurrent validity of the Portuguese version was determined by correlation with data from the actigraphy. An individual data sheet, prepared by the researcher, also included a list of possible ICU sleep stressors, answered by the patients. Patients hospitalized at the postoperative ICU (n = 45) of the Walter Cantídio University Hospital of the Federal University of Ceará, aged 18 years, who were conscious, oriented, literate, hemodynamically stable, and without invasive ventilatory support, participated in the reproducibility and validation phases. prediction of minimumstay in the ICU of 48 hours and signed the informed consent form were included. The original English version of the RCSQ and the back-translated version presented comparability and similarity of interpretation, ensuring that the translation process was satisfactory. The Portuguese version of the questionnaire, applied to patients admitted to the postoperative ICU, was reproducible (intraclass correlation coefficient = 0.925, p <0.001), with good agreement between test and retest and with good internal consistency (alpha coefficient of Cronbach = 0.926). The questionnaire score presented a moderate positive correlation with the sleep efficiency measured by the actigraphy (r = 0.471, p <0.05). On average, the subjective sleep quality of the patients, evaluated through the Portuguese version, was low. The objective evaluation of sleep by the actigraphy revealed, on average, reduced total sleep time (5.98 ± 1.80 h), low sleep efficiency (72.9 ± 15.5%) and high arousal number (25, 9 + 11.2). The main sleep stressors were: lightness (64%), health status (49%), postoperative condition (42%), noise (40%) and invasive procedures and examinations (40%). In conclusion, the results of the present study indicate that the version of RCSQ translated and adapted for use in Brazil is a reproducible, reliable and valid tool for evaluation of sleep quality in intensive care.